Outcome of Percutaneous Endoscopic Interlaminar Lumbar Discectomy. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the outcome of percutaneous endoscopic interlaminar lumbar discectomy for prolapsed intervertebral disc in terms of pain reduction and functional disability.Methods: This descriptive study was conducted in Department of Orthopaedics & Spine Surgery Hayat Abad medical complex Peshawar from 3rd October 2018 to 3rd December 2020.All patients with lumbar disc prolapse fulfilling the inclusion criteria were operated with percutaneous full endoscopic interlaminar lumbar discectomy. Post operative back pain and leg pain was assessed with Visual Analogue Scale(VAS) and functional disability with Oswestry Disability Index (ODI) questionnaire at 2nd week,3rd month and 6th months. Preoperative VAS and ODI was compared with post operative VAS and ODI and P value was calculated with independent-sample t test for statistical significance. P value